Pengaruh E-Service Quality dan E-Trust Terhadap Kepuasan Pengguna Dompet Digital DANA - Halimah, Siti; Novianto, Asep Maulana (Peneliti.net, 2025)
This research aims to find out, analyze and explain the description, correlation, partial influence and simultaneous influence of E-Service Quality and E-Trust on DANA digital wallet user satisfaction. This research uses quantitative methods with descriptive and verification approaches. With a sample of 348 respondents taken from the DANA digital wallet follower population of 838,000 people using a purposive sampling technique. As well as using path analysis and hypothesis testing using the t test and f test. By using Microsoft Excel tools, Method of Successive Interval (MSI), and SPSS version 25 application. Based on the results of the analysis that has been carried out, this research proves that the description of E-Service Quality and E-Trust on DANA digital wallet user satisfaction is included in the quite good category. The correlation coefficient between the variables E-Service Quality and E-Trust obtained a value of 0.721, which means it has a strong, positive and significant correlation level. The partial influence of E-Service Quality on DANA digital wallet user satisfaction is 46.6%, while the partial influence of E-Trust on DANA digital wallet user satisfaction is 31.2%. So it can be stated that E-Service Quality contributes more to satisfaction compared to E-Trust. The simultaneous influence of E-Service Quality and E-Trust on satisfaction is 52.4% while the remaining 47.8% is another variable not examined in this research.